Antenna MIMO 4 Elemen Untuk Komunikasi 5G pada Frekuensi 3.5 GHZ - Ananta Putri Prakusya; Dwi Andi Nurmantris; Radial Anwar - (Universitas Syiah Kuala, 2022)
Cellular communication technology is experiencing rapid development with the arrival of 5G. This generation targets an increase in data rates and better capacity than the previous generation. MIMO is a technique that can be used to improve the performance of 5G communications. The frequency used this time is the middle frequency because it is considered more likely to be used as a 5G service frequency in Indonesia and has a larger coverage so as to save network development costs. In this study, the design and realization of a four-element MIMO antenna for 5G communication at a frequency of 3.5 GHz was carried out. The antenna used this time is a four-element MIMO antenna that has a monopole-based patch form which is then miniaturized so that the antenna has smaller dimensions. This design produces parameters, such as Return Loss on element one of -10.513 dB, for element two of -10.215 dB, for element three of -17.229 dB, and for element four of -14 dB. The value of element one is 1.84, element two is 1.31, element three is 1.31, and element four is 1.49. Bandwidth value ≥ 1500 MHz, and Mutual Coupling value ≤ -19.254 dB.